Novel promising biomarkers in endometrial cancer - review - Dominika Krawczyk; Agnieszka Kwiatkowska (Kazimierz Wielki University, 2019)
Introduction: Endometrial carcinoma is the most common gynaecological neoplasm in developed countries. The disease is mostly asymptomatic at an early stage, however there is no direct marker which could result in detection of cancer earlier. Nowadays the diagnosis is based on the histopathological results of endometrial biopsy. Purpose: The aim of the review was to present the noticable studies that have showed the molecular markers and their usefulness in treatment options of endometrial cancer. We will review the current status of biomarkers which may be helpful in early diagnostic and further therapy of endometrial cancer. State of knowledge: There have been many promising biomarkers which were described in newest studies. TFL is a tumor suppressor gene that contributes to cell-cycle arrest and RNA regulations. CD44 and JAK2 may be liked with neovascularity in distance tissue. Elevated levels of TGM2 and ASRGL1 are associated with an aggressive cancer phenotype and drug resistance in endometrial cancer. Additionally, the level of EpCAM were significantly increased in endometrial cancer sample comparing to control samples. AURKA results in resistance to anticancer agents including paclitaxel and docetaxel used in cancer treatment. Summary: Endometrial cancer is a common problem among gynecological patients. There is no explicit marker which could directly contribute to biologic aggressiveness and response to treatments of that cancer. Presented molecules could potentially be a candidates biomarkers for diagnosis and further treatment of endometrial cancer. However, it is crucial to intensify affords to better understand the impact of these markers. Which could lead to significant improvement of patient's survival and better quality of life.